2022
DOI: 10.1155/2022/2998825
|View full text |Cite|
|
Sign up to set email alerts
|

Postoperative Effect Observation and Clinical Study of Dahuang Zhechong Pills from Jingui Yaolue in Treating Patients with Early-to-Mid Prostate Cancer Undergoing Radical Resection

Abstract: Objective. To explore the effect of applying Dahuang Zhechong pills (DHZCP) from Jingui Yaolue to patients with early-to-mid prostate cancer undergoing radical resection and carry out a theoretical clinical study of traditional Chinese medicine (TCM) to verify the effect of DHZCP formula under the guidance of TCM theory. Methods. The clinical data of 98 patients with early-to-mid prostate cancer undergoing radical resection treated in our hospital (July 2014 to July 2016) were selected for the retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Although certain effects can be achieved, the complication seriously affects patients’ normal life. A 2022 retrospective clinical study consisting of 98 patients undergoing radical resection showed that Dahuang Zhechong Pills improved effective rate of complication treatment at different periods, reduced the biological recurrence rate and clinical recurrence rate ( Hou and Bin, 2022 ).…”
Section: Clinical Practicementioning
confidence: 99%
“…Although certain effects can be achieved, the complication seriously affects patients’ normal life. A 2022 retrospective clinical study consisting of 98 patients undergoing radical resection showed that Dahuang Zhechong Pills improved effective rate of complication treatment at different periods, reduced the biological recurrence rate and clinical recurrence rate ( Hou and Bin, 2022 ).…”
Section: Clinical Practicementioning
confidence: 99%
“…The action of this medicinal formula include dispelling blood stasis and promoting new blood, and its original indications are severe deficiency due to exhaustion or lesions from the five labors: emaciation, fullness in the lower abdomen, loss of appetite, scaly skin, and dark eyes (11). DHZCP could be widely used to treat internal and external conditions, including gynecological diseases, silicosis, and prostate cancer, among others (11)(12)(13)(14). Based on the theory of traditional Chinese medicine, blood stasis that stagnates in the liver can lead to liver diseases (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the theory of traditional Chinese medicine, blood stasis that stagnates in the liver can lead to liver diseases (11,12). Therefore, it has been extensively used to treat various liver diseases, particularly hepatitis and hepatic fibrosis (11)(12)(13)(14). Notably, DHZCP contains various active ingredients, such as anthraquinones, flavonoids, amino acids, and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled “Postoperative Effect Observation and Clinical Study of Dahuang Zhechong Pills from Jingui Yaolue in Treating Patients with Early-to-Mid Prostate Cancer Undergoing Radical Resection” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%